Weight Gain in Infancy and Childhood Were Associated With Pubertal Development in Boys and Girls - Nummela, Saga Rebecca; Pahkala, Katja; Karppinen, Sinikka; Toppari, Jorma; Raitakari, Olli; Niinikoski, Harri (WILEY, 2025)
Aim As earlier puberty has been associated with higher later metabolic risk, we studied how weight gain in infancy and childhood is associated with pubertal timing and duration in healthy children.
Method Leveraging the longitudinal data from the Special Turku Coronary Risk Factor Intervention Project study, we used linear regression analyses to investigate how weight gain in different age intervals during infancy and childhood is associated with the onset, culmination and duration of puberty in 230 boys and 278 girls.
Results For girls, a 1 standard deviation (SD) greater weight gain in infancy and childhood predicted earlier onset of breast development and earlier menarche by approximately 3-4 months. For boys, a 1 SD greater weight gain in infancy and childhood predicted earlier start and culmination of genital development according to Tanner stages by approximately 2 months. Greater weight gain in infancy and childhood seems to lengthen the duration of puberty in girls by 1-2 months, but is not associated with the duration of puberty in boys.
Conclusions Weight gain in infancy and childhood was associated with the timing of puberty in both boys and girls.